A relação entre a política monetária e a gestão da dívida pública mobiliária no México (1995-2015) - Prates, Daniela Magalhães; Blikstad, Nicholas (Brazilian Keynesian Review, 2018)
The significant growth of reverse repo operations and its impact on the gross public debt raised recently an intensive debate on the relationship between the monetary authority and the National Treasury in the management of the public securities debt. This article aims to contribute to this debate with the case study of Mexico, Latin American country with a similar insertion in the contemporary international monetary and financial system and economic characteristics most closely resembling Brazil. The comparative perspective will enable to grasp if the current features of that debt and the monetary policy implementation in Brazil are, in fact, unique. If the particularity of of the Brazilian case is confirmed, its comparison with the Mexican experience will be fruitful for the understanding of its implications for the effectiveness and costs of monetary policy, providing support for the formulation of policy recommendations.